Application of LEISA to Scale Up Products and Increase Entrepreneurial Capacity of Melennial Farmers in Balunijuk Village - Rufti Puji Astuti; Tri Lestari (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2022)
Balunijuk Village is a production center for horticultural products in Bangka Regency, and the majority of its people work as farmers. This service activity aims to provide assistance in implementing the LEISA system, encouraging the scale up of its products, and increasing the entrepreneurial capacity of millennial farmers in the Taruna mandiri farmer group through mastery of technology. The activity was carried out in Balunjuk Village, Merawang District, Bangka Regency, Kepulauan Bangka Belitung Province. The service activities carried out went through 6 (six) stages of activities, namely polyculture techniques, training in making liquid organic fertilizer (POC), training in making animal feed, duck and fish farming, socialization and promotion activities. The results of the application of the LEISA technology package by combining polyculture vegetable cultivation techniques, duck farming and intensive mentoring. Through this community empowerment program, we can reduce the use of chemical fertilizers and chemical pesticides that endanger health and damage the environment. The use of chemical fertilizers can be replaced with compost, liquid organic fertilizer (POC), while chemical pesticides can be replaced with vegetable pesticides. The socialization activities were carried out using presentation methods and interactive discussions that contained all questions and positive responses from the guests/audience.